The effects of a combined psychotherapy and physiotherapy group treatment program for survivors of torture incarcerated in an adult prison in Kurdistan, Iraq: A pilot study - Gamble, April; Amin Ahmed, Ahmed M.; Hassan Rahim, Salah; Hartman, Jeff (Torture Journal, 2020)
Introduction: Survivors of torture have high rates of mental health problems and can experience a sequela of physical effects with the most common being persistent pain. Similar to survivors of torture, persons that are incarcerated have high rates of mental health problems, persistent pain and pain-related disability.The purpose of this study is to assess the effect of an interdisciplinary group treatment approach, involving psychotherapy and physiotherapy, with survivors of torture whom are incarcerated in a prison in Kurdistan, Iraq. Methods: A parallel group study design was used to compare a treatment group (n=11) and a wait-list control group (n=16). The treatment group participated in an interdisciplinary treatment service for a total of 10 weekly group sessions for each discipline.The primary outcome measures were symptoms of nociplastic pain, anxiety, depression, and PTSD. Secondary outcome measures evaluated physical functioning, sleep quality, and general self-efficacy. Results: A statistically significant reduction in outcome measure scores was seen in all symptoms measured immediately post-treatment. Discussion and Conclusion: These findings suggest that a culturally and contextually appropriate interdisciplinary group treatment intervention for survivors of torture in a prison could be effective for short-term reductions in symptoms of anxiety, depression, PTSD, persistent pain, and function. The study has limitations including a small sample size, lack of long-term outcome measures, and an inability to isolate effect of each component of care. The study does demonstrate the feasibility of implementing research that follows international research standards and practices within under-researched settings and post-conflict areas.